2019
DOI: 10.3390/metabo9100203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Storage Conditions and Preservatives on Metabolite Fingerprints in Urine

Abstract: Human urine, which is rich in metabolites, provides valuable approaches for biomarker measurement. Maintaining the stability of metabolites in urine is critical for accurate and reliable research results and subsequent interpretation. In this study, the effect of storage temperature (4, 22, and 40 °C), storage time (24 and 48 h), and use of preservatives (boric acid (BA), thymol) and para-aminobenzoic acid (PABA) on urinary metabolites in the pooled urine samples from 20 participants was systematically investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…For urine samples, AssayAssure minimizes alterations in the microbial community if urine samples are to be stored at room temperature for longer than 1 h 31 ; if urine samples are frozen within 1 h, AssayAssure is not needed. Of note, neither boric acid nor AssayAssure is recommended if downstream metabolomic assays or other clinical assays are planned, such as a 24-h urine collection for metabolic risk factors, as boric acid or other preservatives lead to substantial alterations of the urinary metabolites 31 , 32 . In these cases, the consortium recommends that an aliquot of urine is subsampled and placed into preservative for downstream microbiome analyses, whereas another sample without preservative is used for metabolomic analyses.…”
Section: Resultsmentioning
confidence: 99%
“…For urine samples, AssayAssure minimizes alterations in the microbial community if urine samples are to be stored at room temperature for longer than 1 h 31 ; if urine samples are frozen within 1 h, AssayAssure is not needed. Of note, neither boric acid nor AssayAssure is recommended if downstream metabolomic assays or other clinical assays are planned, such as a 24-h urine collection for metabolic risk factors, as boric acid or other preservatives lead to substantial alterations of the urinary metabolites 31 , 32 . In these cases, the consortium recommends that an aliquot of urine is subsampled and placed into preservative for downstream microbiome analyses, whereas another sample without preservative is used for metabolomic analyses.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the variation introduced by this complexation process was negligible in comparison with inter-individual variations, so borate preservation was proposed as a suitable method for 1 H-NMR-based metabolomics, although special caution should be paid in the assignment of signals for metabolites having diol or adjacent hydroxyl and carboxylate groups. Similarly, Wang et al also found that boric acid provokes metabolite changes in urine, and instead, recommended the use of thymol [65]. Nonetheless, they also demonstrated that urine metabolite concentrations remain stable at 4 • C for up to 48 h, thus showing that the use of additives is not mandatory.…”
Section: Pre-processing Of Urine Samplesmentioning
confidence: 99%
“…To the best of our knowledge, however, this strategy is not widely used (at least in hospitals for diagnostic routine purposes). Wang et al reported effective stabilization of a metabolite profile of 158 urinary metabolites by thymol, while the addition of boric acid caused alterations of the metabolome (n = 20 participants) detected by LC-MS [71]. Additionally, Lauridsen et al tested other inhibitors and demonstrated that the use of 0.1% sodium azide is not critical for NMR spectra; however, 1% sodium fluoride led to shifts [67].…”
Section: Cooling During Collection and Transportation Preserves The Metabolomementioning
confidence: 99%